Grow younger, live longer : 10 steps to reverse aging - Chopra, Deepak. frey50; Simon, David, 1951- (New York : Harmony Books, 2001)
An ecstatic journey into the miracle of age reversal by two of the finest physicians and thinkers of our time. "Grow Younger, Live Longer" provides you with every tool to dramatically reverse you biological age. Willingly suspend your disbelief and observe yourself growing younger in every way.
Keywords: Longevity; Aging. -- Prevention